Lead paste for lead-acid battery and preparation process of lead paste

By introducing modified graphene and high-strength staple fibers into lead-acid battery lead paste, the problems of falling off the active substances of traditional lead paste, increasing internal resistance and insufficient mechanical strength are solved, and the service life and electrochemical performance of the battery are significantly improved.

CN119481066AInactive Publication Date: 2025-02-18JIESHOU HUAYU POWER SUPPLY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411646396.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the charging and discharging process of traditional lead-acid battery lead paste, the active substances are prone to fall off, the internal resistance increases, the performance of high and low temperatures is poor, and the mechanical strength is insufficient, resulting in a decrease in battery capacity, shortened service life and poor stability.

Method used

The raw materials such as lead powder, modified graphene, high-strength staple fiber, trilead tetraoxide, tetrabase lead sulfate, bismuth oxide, stannous sulfate, sulfuric acid solution and deionized water are used to adopt specific preparation processes, including dry mixing, By stirring, defoaming and forming, a lead paste for lead-acid batteries is prepared.

Benefits of technology

By introducing modified graphene and high-strength staple fibers, the bonding between the lead paste and the grid is significantly enhanced, the active substances are removed, the mechanical strength and electrochemical performance are improved, the battery life is extended, and the battery's internal resistance is reduced. , improve charging acceptance and discharge efficiency.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses lead paste for a lead-acid battery and a preparation process of the lead paste, and belongs to the technical field of lead-acid batteries, the lead paste comprises the following raw materials in parts by weight: 90-100 parts of lead powder, 0.1-0.2 part of high-strength short fiber, 15-20 parts of lead tetraoxide, 1-1.5 parts of tetrabasic lead sulfate, 5-12 parts of modified graphene, 0.2-0.3 part of bismuth oxide, 0.1-0.15 part of stannous mono-sulphate, 10-15 parts of sulfuric acid solution and 8-16 parts of deionized water; the modified graphene is prepared by the following steps: uniformly mixing concentrated sulfuric acid and sodium nitrate in a reaction flask, and slowly adding graphite powder under an ice-water bath condition. By optimizing the formula and the preparation process of the lead paste for the lead-acid battery, and particularly introducing the modified graphene, the conductivity and the thermal stability of the lead paste are remarkably improved, the binding force between the lead paste and a grid is enhanced, and the falling of active substances is reduced, so that the cycle life of the battery is remarkably prolonged, and the capacity of the battery is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lead-acid batteries, and in particular relates to a lead paste for lead-acid batteries and a preparation process thereof. Background Art

[0002] Lead-acid batteries are a type of chemical power source widely used in automobile starting, lighting, communications, power system backup power, etc. Their performance and service life are directly affected by the composition and preparation process of lead paste. Lead paste is one of the most critical active substances in lead-acid batteries. It not only determines the electrochemical performance of the battery, but also affects the cycle life and safety of the battery.

[0003] Traditional lead-acid battery lead paste is mainly composed of lead powder, sulfuric acid solution and water, and sometimes a small amount of additives such as short fibers and lignin are added to improve the physical and chemical properties of the lead paste. Although these traditional formulas have met the early application needs to a certain extent, they still have some obvious defects in the face of the requirements of modern high-performance batteries:

[0004] 1. Active material shedding: During the battery charging and discharging process, the active material in the traditional lead paste easily falls off from the grid, causing the battery capacity to gradually decrease and shortening the battery life;

[0005] 2. Increased internal resistance: During the use of traditional lead paste, due to the uneven distribution of active substances and the poor formation of the interface corrosion layer, the internal resistance of the battery gradually increases, reducing the battery's charging acceptance and discharge efficiency;

[0006] 3. Poor performance at high and low temperatures: Traditional lead paste performs poorly under extreme temperature conditions, especially in high temperature environments, where the self-discharge rate of the battery increases, while in low temperature environments, the discharge capacity of the battery decreases significantly;

[0007] 4. Insufficient mechanical strength: Traditional lead paste has low mechanical strength and is easily physically damaged during transportation and use, affecting the stability and reliability of the battery. Summary of the invention

[0008] The object of the present invention is to provide a lead paste for lead-acid batteries and a preparation process thereof, so as to solve the following technical problems: active material shedding of the lead paste, increased internal resistance, poor high and low temperature performance and insufficient mechanical strength.

[0009] The purpose of the present invention can be achieved through the following technical solutions:

[0010] A lead paste for a lead-acid battery, comprising the following raw materials in parts by weight: 90-100 parts of lead powder, 0.1-0.2 parts of high-strength short fibers, 15-20 parts of lead tetroxide, 1-1.5 parts of tetrabasic lead sulfate, 5-12 parts of modified graphene, 0.2-0.3 parts of bismuth oxide, 0.1-0.15 parts of stannous sulfate, 10-15 parts of sulfuric acid solution, and 8-16 parts of deionized water;

[0011] The modified graphene comprises the following steps of preparation:

[0012] Step 1: Evenly mix concentrated sulfuric acid and sodium nitrate in a reaction bottle, slowly add graphite powder in an ice-water bath, continue stirring for 1-1.5 hours, then remove the ice bath, transfer the reaction bottle to an electromagnetic stirrer, continue stirring at room temperature for 10-12 hours, and finally slowly add deionized water, heat to 90-98°C, and continue stirring for 0.8-1.2 hours to obtain crude graphite oxide;

[0013] Step 2: adding hydrogen peroxide to the crude graphite oxide, centrifuging and washing until the pH value of the supernatant is close to neutral, and then dispersing the cleaned graphite oxide in deionized water and performing ultrasonic treatment for 2-4 hours to form graphene oxide;

[0014] Step three, add the graphene oxide formed by ultrasonic treatment to the saturated fatty acid saponification liquid and stir ultrasonically for 1-2 hours to perform the first surface modification, then filter, dry and grind the graphene after the first modification, add it to a high-speed mixer, control the material temperature to 60-80°C, add a second surface treatment agent composed of distearylethyl glycidyl ammonium chloride and bisamide sulfonyl betaine ester, stir ultrasonically for 1-2 hours, perform the second surface modification, and finally dry it at 60-80°C for 10-12 hours to obtain modified graphene.

[0015] As a further solution of the present invention, the usage ratio of concentrated sulfuric acid, sodium nitrate, graphite powder and deionized water in step 1 is 20-25 ml: 0.8-1.2 g: 1-3 g: 200-250 ml.

[0016] As a further solution of the present invention, the usage ratio of the crude graphite oxide, hydrogen peroxide and deionized water in step 2 is 2-4g:10-15ml:100-150ml.

[0017] As a further solution of the present invention, the usage ratio of the graphene oxide, saturated fatty acid saponification liquid, distearylethyl glycidyl ammonium chloride, and bisamide type sulfobetaine ester in step three is 1-3g:100-150ml:0.5-1g:1-2g.

[0018] As a further embodiment of the present invention, a process for preparing lead paste for lead-acid batteries comprises the following preparation steps:

[0019] The raw materials are weighed according to the formula, lead powder, high-strength short fiber, lead tetraoxide, tetrabasic lead sulfate, bismuth oxide and stannous sulfate are added to a paste making machine and dry mixed for 3-5 minutes, modified graphene is added and dry mixed for 1-2 minutes, deionized water is slowly added and stirred for 2-3 minutes, sulfuric acid solution is slowly added and stirred for 4-6 minutes, the mixed lead paste is added to a vacuum degassing machine for degassing, the degassed lead paste is poured into a mold for molding, and finally the molded lead paste is solidified to obtain a lead paste for lead-acid batteries.

[0020] As a further solution of the present invention, the deionized water is added for 1-2 minutes, the sulfuric acid solution is added for 3-5 minutes, and the paste mixing machine rotates at a speed of 120-200 r / min.

[0021] Beneficial effects of the present invention:

[0022] 1. In the present invention, by introducing modified graphene, high-strength short fibers and bismuth oxide, the modified graphene has excellent conductivity and thermal stability, can significantly enhance the bonding force between the lead paste and the grid, during the charge and discharge process, the modified graphene can form a stable conductive network to reduce the shedding of active substances, the high-strength short fibers can enhance the mechanical strength of the lead paste to prevent the active substances from shedding due to physical damage during transportation and use, the high-strength short fibers and the modified graphene work synergistically to further improve the stability and durability of the lead paste, the enhanced mechanical strength not only improves the appearance quality of the battery, but also enhances the internal structural stability of the battery, and prolongs the service life of the battery, bismuth oxide as a pore former can improve the pore structure of the lead paste and improve the utilization rate of the active substances, during the charge and discharge process, bismuth oxide can promote the uniform distribution of active substances, reduce local overheating and uneven chemical reactions, and thus prolong the service life of the battery.

[0023] 2. In the present invention, by reasonably matching lead powder, high-strength short fibers, lead tetroxide, tetrabasic lead sulfate, modified graphene, bismuth oxide, stannous sulfate, sulfuric acid solution and deionized water, it is possible to promote the formation of a good interface corrosion layer, reduce the internal resistance of the battery, and improve the charging acceptance and discharge efficiency. Lead tetroxide and tetrabasic lead sulfate can improve the electrical conductivity and chemical stability of the lead paste and reduce the internal resistance of the battery during the charging and discharging process. Lead tetroxide, as a part of the active substance, can improve the initial capacity and cycle stability of the battery. Tetrabasic lead sulfate can promote the uniform distribution of the lead paste and reduce local overheating, thereby improving the electrochemical performance of the battery. Stannous sulfate, as an interface conductivity improver, can promote good contact between the lead paste and the grid and reduce contact resistance. During the charging and discharging process, stannous sulfate can improve the charging acceptance of the battery, reduce the charging time, and improve the discharge efficiency of the battery. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Example 1

[0026] A modified graphene comprises the following steps of preparation:

[0027] Mix 200 ml of concentrated sulfuric acid and 8 g of sodium nitrate in a reaction bottle, slowly add 10 g of graphite powder in an ice-water bath, continue stirring for 1 hour, then remove the ice bath, transfer the reaction bottle to an electromagnetic stirrer, continue stirring at room temperature for 10 hours, finally slowly add 2000 ml of deionized water, heat to 90°C, and continue stirring for 0.8 hours to obtain crude graphite oxide;

[0028] Step 2: Add 100 ml hydrogen peroxide to 20 g crude graphite oxide, centrifuge and wash until the pH value of the supernatant is close to neutral, then disperse the cleaned graphite oxide in 1000 ml deionized water and perform ultrasonic treatment for 2 hours to form graphene oxide;

[0029] Step 3: Add 10 g of graphene oxide formed by ultrasonic treatment to 1000 ml of saturated fatty acid saponification solution and stir ultrasonically for 1 hour for the first surface modification, then filter, dry and grind the graphene after the first modification, add it to a high-speed mixer, control the material temperature to 60°C, add 5 g of distearylethyl ammonium chloride and 10 g of bisamide sulfonyl betaine ester as the second surface treatment agent, stir ultrasonically for 1 hour, carry out the second surface modification, and finally dry it at 60°C for 10 hours to obtain the modified graphene.

[0030] Example 2

[0031] A modified graphene comprises the following steps of preparation:

[0032] Step 1: Evenly mix 250 ml concentrated sulfuric acid and 12 g sodium nitrate in a reaction bottle, slowly add 30 g graphite powder in an ice-water bath, continue stirring for 1.5 h, then remove the ice bath, transfer the reaction bottle to an electromagnetic stirrer, continue stirring at room temperature for 12 h, finally slowly add 2500 ml deionized water, heat to 98 ° C, continue stirring for 1.2 h, and obtain crude graphite oxide;

[0033] Step 2: Add 150 ml hydrogen peroxide to 40 g crude graphite oxide, centrifuge and wash until the pH value of the supernatant is close to neutral, then disperse the cleaned graphite oxide in 2500 ml deionized water and perform ultrasonic treatment for 4 hours to form graphene oxide;

[0034] Step 3: Add 30 g of graphene oxide formed by ultrasonic treatment to 1500 ml of saturated fatty acid saponification solution and stir ultrasonically for 2 hours to perform the first surface modification. Then, the graphene after the first modification is filtered, dried, and ground, and added to a high-speed mixer. The material temperature is controlled to 80°C, and a second surface treatment agent consisting of 10 g of distearylethyl glycidyl ammonium chloride and 20 g of bisamide sulfonyl betaine ester is added. Stir ultrasonically for 2 hours, perform the second surface modification, and finally dry at 80°C for 12 hours to obtain modified graphene.

[0035] Example 3

[0036] A process for preparing lead paste for lead-acid batteries, comprising the following preparation steps:

[0037] The raw materials were weighed according to the formula, 90g of lead powder, 0.1g of high-strength short fiber, 15g of lead tetraoxide, 1g of tetrabasic lead sulfate, 0.2g of bismuth oxide and 0.1g of stannous sulfate were added to a paste mixer and dry mixed for 3min, the speed of the paste mixer was 120r / min, 5g of the modified graphene obtained in Example 1 was added and continued to be dry mixed for 1min, 8g of deionized water was slowly added and stirred for 2min, the addition time of deionized water was 1min, 10g of sulfuric acid solution was slowly added and continued to be stirred for 4min, the addition time of sulfuric acid solution was 3min, the mixed lead paste was added to a vacuum degassing machine for degassing treatment, the degassed lead paste was poured into a mold for molding, and finally the molded lead paste was cured to obtain a lead paste for lead-acid batteries.

[0038] Example 4

[0039] A process for preparing lead paste for lead-acid batteries, comprising the following preparation steps:

[0040] The raw materials were weighed according to the formula, 100 g of lead powder, 0.2 g of high-strength short fiber, 20 g of lead tetraoxide, 1.5 g of tetrabasic lead sulfate, 0.3 g of bismuth oxide and 0.15 g of stannous sulfate were added to a paste mixer and dry mixed for 5 min, the speed of the paste mixer was 200 r / min, 12 g of the modified graphene obtained in Example 1 was added and continued to be dry mixed for 2 min, 16 g of deionized water was slowly added and stirred for 3 min, the addition time of deionized water was 2 min, 15 g of sulfuric acid solution was slowly added and continued to be stirred for 6 min, the addition time of sulfuric acid solution was 5 min, the mixed lead paste was added to a vacuum degassing machine for degassing treatment, the degassed lead paste was poured into a mold for molding, and finally the molded lead paste was cured to obtain a lead paste for lead-acid batteries.

[0041] Comparative Example 1

[0042] A modified graphene comprises the following steps of preparation:

[0043] Mix 200 ml of concentrated sulfuric acid and 8 g of sodium nitrate in a reaction bottle, slowly add 10 g of graphite powder in an ice-water bath, continue stirring for 1 hour, then remove the ice bath, transfer the reaction bottle to an electromagnetic stirrer, continue stirring at room temperature for 10 hours, finally slowly add 2000 ml of deionized water, heat to 90°C, and continue stirring for 0.8 hours to obtain crude graphite oxide;

[0044] Step 2: Add 100 ml hydrogen peroxide to 20 g crude graphite oxide, centrifuge and wash until the pH value of the supernatant is close to neutral, then disperse the cleaned graphite oxide in 1000 ml deionized water and perform ultrasonic treatment for 2 hours to form graphene oxide;

[0045] Step 3: Add 10 g of graphene oxide formed by ultrasonic treatment to 1200 ml of saturated fatty acid saponification solution and stir ultrasonically for 1 hour for the first surface modification, then filter, dry and grind the graphene after the first modification, add it to a high-speed mixer, control the material temperature to 60°C, add 5 g of distearylethyl glycidyl ammonium chloride and 10 g of bisamide sulfonyl betaine ester as the second surface treatment agent, stir ultrasonically for 1 hour, carry out the second surface modification, and finally dry it at 60°C for 10 hours to obtain the modified graphene.

[0046] Compared with Example 1, this comparative example only replaces "1000 ml of saturated fatty acid saponification liquid" with "1200 ml of saturated fatty acid saponification liquid", and the remaining steps and parameters are the same.

[0047] Comparative Example 2

[0048] A process for preparing lead paste for lead-acid batteries, comprising the following preparation steps:

[0049] The raw materials were weighed according to the formula, 90g of lead powder, 0.1g of high-strength short fiber, 15g of lead tetraoxide, 1g of tetrabasic lead sulfate, 0.2g of bismuth oxide and 0.1g of stannous sulfate were added to a paste mixer and dry mixed for 3min, the speed of the paste mixer was 120r / min, 5g of the modified graphene obtained in Example 1 was added and continued to be dry mixed for 1min, 8g of deionized water was slowly added and stirred for 2min, the addition time of deionized water was 1min, 10g of sulfuric acid solution was slowly added and continued to be stirred for 4min, the addition time of sulfuric acid solution was 3min, the mixed lead paste was added to a vacuum degassing machine for degassing treatment, the degassed lead paste was poured into a mold for molding, and finally the molded lead paste was cured to obtain a lead paste for lead-acid batteries.

[0050] Compared with Example 3, this comparative example only replaces "5 g of modified graphene obtained in Example 1" with "5 g of graphene", and the remaining steps are the same.

[0051] Comparative Example 3

[0052] A process for preparing lead paste for lead-acid batteries, comprising the following preparation steps:

[0053] The raw materials were weighed according to the formula, 90g of lead powder, 0.1g of high-strength short fiber, 15g of lead tetraoxide, 1g of tetrabasic lead sulfate, 0.2g of bismuth oxide and 0.1g of stannous sulfate were added to a paste mixer and dry mixed for 3min, the speed of the paste mixer was 120r / min, 5g of the modified graphene obtained in Comparative Example 1 was added and continued to be dry mixed for 1min, 8g of deionized water was slowly added and stirred for 2min, the addition time of deionized water was 1min, 10g of sulfuric acid solution was slowly added and continued to be stirred for 4min, the addition time of sulfuric acid solution was 3min, the mixed lead paste was added to a vacuum degassing machine for degassing treatment, the degassed lead paste was poured into a mold for molding, and finally the molded lead paste was cured to obtain a lead paste for lead-acid batteries.

[0054] Compared with Example 3, this comparative example only replaces "5 g of modified graphene obtained in Example 1" with "5 g of modified graphene obtained in Comparative Example 1", and the remaining steps and parameters are the same.

[0055] The lead paste for lead-acid batteries prepared in Example 3-4 and Comparative Example 2-3 was subjected to the following performance tests:

[0056] (1) Resistivity test: GB / T 7403.1-2-2018 "Lead-acid batteries for traction - Part 1-2 (combined)", the resistivity of lead paste is measured using the four-probe method;

[0057] (2) Bonding strength test: According to GB / T 38279-2019 Technical Specification for Auxiliary Materials for Lead-acid Batteries, the bonding strength between the lead paste and the grid is measured by a tensile test;

[0058] (3) Discharge efficiency test: According to GB / T 32504-2016 "Safety Technical Specifications for Civil Lead-acid Batteries", the discharge efficiency of the battery is measured through a constant current discharge test; the test results are shown in Table 1:

[0059] Table 1

[0060] project Resistivity (Ω·cm) Binding force (N) Discharge efficiency (%) Example 3 0.34 6.5 92 Example 4 0.38 6.2 90 Comparative Example 2 0.52 4.6 80 Comparative Example 3 0.46 5.3 86

[0061] It can be seen from Table 1 that the lead paste for lead-acid batteries prepared in Examples 3-4 of the present invention has not only higher binding force but also lower resistivity than the lead paste for lead-acid batteries prepared in Comparative Examples 2-3, and the lead-acid battery using the lead paste has higher discharge efficiency.

[0062] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0063] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A lead paste for lead-acid batteries, characterized in that: The invention comprises the following raw materials in parts by weight: 90-100 parts of lead powder, 0.1-0.2 parts of high-strength short fibers, 15-20 parts of lead tetroxide, 1-1.5 parts of tetrabasic lead sulfate, 5-12 parts of modified graphene, 0.2-0.3 parts of bismuth oxide, 0.1-0.15 parts of stannous sulfate, 10-15 parts of sulfuric acid solution, and 8-16 parts of deionized water; The modified graphene comprises the following steps of preparation: Step 1: Evenly mix concentrated sulfuric acid and sodium nitrate in a reaction bottle, slowly add graphite powder in an ice-water bath, continue stirring for 1-1.5 hours, then remove the ice bath, transfer the reaction bottle to an electromagnetic stirrer, continue stirring at room temperature for 10-12 hours, and finally slowly add deionized water, heat to 90-98°C, and continue stirring for 0.8-1.2 hours to obtain crude graphite oxide; Step 2: adding hydrogen peroxide to the crude graphite oxide, centrifuging and washing until the pH value of the supernatant is close to neutral, and then dispersing the cleaned graphite oxide in deionized water and performing ultrasonic treatment for 2-4 hours to form graphene oxide; Step three, add the graphene oxide formed by ultrasonic treatment to the saturated fatty acid saponification liquid and stir ultrasonically for 1-2 hours to perform the first surface modification, then filter, dry and grind the graphene after the first modification, add it to a high-speed mixer, control the material temperature to 60-80°C, add a second surface treatment agent composed of distearylethyl glycidyl ammonium chloride and bisamide sulfonyl betaine ester, stir ultrasonically for 1-2 hours, perform the second surface modification, and finally dry it at 60-80°C for 10-12 hours to obtain modified graphene.

2. The lead paste for lead-acid batteries according to claim 1, characterized in that: The dosage ratio of concentrated sulfuric acid, sodium nitrate, graphite powder and deionized water in step 1 is 20-25 ml: 0.8-1.2g: 1-3g: 200-250ml.

3. The lead paste for lead-acid batteries according to claim 1, characterized in that: In step 2, the usage ratio of the crude graphite oxide, hydrogen peroxide and deionized water is 2-4g: 10-15ml: 100-150ml.

4. The lead paste for lead-acid batteries according to claim 1, characterized in that: In step 3, the usage ratio of graphene oxide, saturated fatty acid saponification liquid, distearylethyl glycidyl ammonium chloride, and bisamide sulfobetaine ester is 1-3g:100-150ml:0.5-1g:1-2g.

5. A process for preparing a lead paste for a lead-acid battery according to any one of claims 1 to 4, characterized in that: The method comprises the following preparation steps: The raw materials are weighed according to the formula, lead powder, high-strength short fiber, lead tetraoxide, tetrabasic lead sulfate, bismuth oxide and stannous sulfate are added to a paste making machine and dry mixed for 3-5 minutes, modified graphene is added and dry mixed for 1-2 minutes, deionized water is slowly added and stirred for 2-3 minutes, sulfuric acid solution is slowly added and stirred for 4-6 minutes, the mixed lead paste is added to a vacuum degassing machine for degassing, the degassed lead paste is poured into a mold for molding, and finally the molded lead paste is solidified to obtain a lead paste for lead-acid batteries.

6. The process for preparing the lead paste for lead-acid batteries according to claim 5, characterized in that: The deionized water is added for 1-2 minutes, the sulfuric acid solution is added for 3-5 minutes, and the paste mixing machine rotates at 120-200 r / min.

Citation Information

Patent Citations

  • Preparation method for modified graphene

    CN108395736A

  • Lead paste for improving utilization rate of positive active substance of lead-acid storage battery and preparation method of lead paste

    CN109616666A

  • Positive electrode lead paste of lead-acid storage battery, preparation method of positive electrode lead paste and lead-acid storage battery

    CN112290017A

  • Positive lead paste of lead-acid storage battery and preparation method of positive lead paste

    CN114335453A